Gênero e poder: o pastorado feminino na Igreja Batista - Lima, Wamberto Queiroz de (2011)
The object of this research is the analysis of reports on gender and power in the forms of discrimination against women in the process of formation, and recognition as pastors in the Baptist Church for the year of the pastorate. The significance of this is partly because of making visible the ethical-religious prejudice and discrimination against women pastors, because this church presents itself as the frontrunner because he is one of the few churches that ordain women accept to be pastors, but in practice is not really so. The goal of this research was: To analyze the discursive content expressed by ordained Baptist Church of Paraiba regarding their experiences in the structure of power relations within this established formal institution, whose upper bodies are reluctant to accept the pastorate female. This was a qualitative study guided by data collection and document the life stories of two pastors of this religious institution. Data from the interviews to capture the life stories were analyzed in the light of the phenomenological method, which emphasizes the subjectivity of the collaborators. I found that even though this church is to accept the avant-garde female grazing, which has not occurred in other traditional evangelical churches, there are numerous and subtle discrimination against ordained ministers, especially in regard to its ascent to higher positions in the power structure of higher levels of the Order of the Baptist Pastors at state and national, as well as the Brazilian Baptist Convention. Thus, they have conformed to the assignment of work less important than that of male pastors, for example, accept to be in support of senior pastors or carry positions related to the grazing of women, which does not give them access to decision-making Baptists of the higher commands. I also noted that the pastors themselves discriminate and exclude themselves from participation in meetings of the commands of leaders of this institution. This research This research was inspired by theorists such as Scott (1990), Nolasco (1995), Ranke-Heinemann (1996), Oliveira (RD, 1999), Louro (2001) and analysts Queer theory as Seidman (1995) among others.